Adaptive Frequency-Based Power Management for Off-Grid Hybrid Photovoltaic Converters - Gonschorowski, Ezequiel; Cardoso, Rafael; Carvalho, Edivan Laercio; Stein, Carlos Marcelo de Oliveira; Carati, Emerson Giovani; Denardin, Gustavo Weber; da Costa, Jean Patric (Eletrônica de Potência, 2024)
The intermittency in photovoltaic systems (PV) can lead to power quality issues, especially in off-grid applications. In these cases, adding an energy storage element helps to cope with the intermittency to provide adequate power to the local load. In this scenario, combining Li-Ion batteries and supercapacitors as a hybrid energy storage system (HESS) is powerful due to the battery’s high energy density and the supercapacitor’s high power density. The HESS demands adequate power management to operate adequately. This paper proposes an adaptive frequency-based power management for a Li-Ion battery and supercapacitor HESS applied to an off-grid PV converter. The main idea of this strategy is to guarantee a smoother current in the battery and reduce the power dissipation in the HESS. The smoother battery current transition helps avoid excessive battery stress and improves lifespan. The proposed strategy is compared with two other strategies. The results show that the proposed approach is more efficient in reducing the HESS’ power dissipation and providing smooth current variations to the battery.